Feasibility of ranching coastal cod in Northwest Iceland - Jón Eðvald Halldórsson (2009)
An experiment on ranching wild, free-ranging cod in an Icelandic fjord was conducted in Arnarfjördur, Northwest Iceland, in the years 2005-2006. Regular feeding with cheap pelagic fish formed four sizable herds of cod. The cod in the herds showed enormous growth rate and high fidelity to their herds. Based on this experiment, a feasibility study of ranching wild cod in an open fjord was carried out. The hypothesis is that ranching of cod by anthropogenic feeding improves growth rates and enhances quota yield without the considerable investments required in cod farming. For ranching cod, five different scenarios were analysed, emphasising capturing and harvesting strategies. For comparison, a similar feasibility study was made for three alternatives: on-growing of wild cod in sea cages; full-cycle cod farming using hatchery produced juveniles; and commercial cod fishery. It was assumed in the calculations that a 200 ton quota is either used for fishing, ranching or on-growing in sea cages. The results indicate that ranching is the most profitable option, fishing the second and on-growing in third place. Full-cycle cod farming was found to be unprofitable, due to high production cost. Of the five ranching scenarios investigated, which all were profitable, ranching on a larger scale was the most viable option. When considering the four smaller scale alternatives, harvesting cod larger than 2.5 kg and on-growing the smaller cod for a second year in sea cages was considered the most feasible option. Tækniþróunarsjóður